The Relationship between the Risks of Aggression among University Students and Indicators of Self-Efficacy, Self-Esteem, and Humility - A.A. Rean; A.V. Egorova; I.A. Konovalov; A.A. Stavtsev; A.O. Shevchenko; R.G. Kuzmin (Психологическая наука и образование)
The study focuses on comparing rates of self-efficacy, self-esteem, and humility in relation to levels of physical aggression, anger, hostility, and general aggressiveness. 2315 students (83% – female) from Russian universities were recruited for this study. The following methods were utilized: the Buss-Perry Aggression Questionnaire, Rosenberg's Self-Esteem Scale, R. Schwarzer's & M. Jerusalem's General Self-efficacy scale, S. Shwartz's Values Questionnaire (PVQ-R2). Data from the "Humility" scale was used. The results showed significant negative correlations between the mentioned variables. An increase of aggression rates is associated with a decrease in self-efficacy, self-esteem, and humility. It was also found that there was no relationship between the indicators of hostility and humility. It was shown that the indicators of self-efficacy, self-esteem and humility differ in the context of different types of aggression. It was found that students with low and medium levels of physical aggression are characterized by higher indicators of self-efficacy, self-esteem, and humility. A similar trend is relevant for the group with low level of anger. Students with low levels of hostility show higher scores of self-efficacy and self-esteem (but not humility). Students' self-esteem, humility, and self-efficacy also vary in the context of aggressiveness integral measure levels. The obtained results can be applied in the implementation of the Concept of development of the network of psychological services in educational organizations of higher education in the Russian Federation.